Effect of epidermal growth factor-like peptides on pig cumulus cell expansion, oocyte maturation, and acquisition of developmental competence in vitro: comparison with gonadotropins - Procházka, Radek; Petlach, Michal; Nagyová, Eva; Nemcová, Lucie (Reproduction, 2011)
The aim of this work was to assess the FSH-stimulated expression of epidermal growth factor (EGF)-like peptides in cultured cumulus-oocyte complexes (COCs) and to find out the effect of the peptides on cumulus expansion, oocyte maturation, and acquisition of developmental competence in vitro. FSH promptly stimulated expression of amphiregulin (AREG) and epiregulin (EREG), but not betacellulin (BTC) in the cultured COCs. Expression of AREG and EREG reached maximum at 2 or 4 h after FSH addition respectively. FSH also significantly stimulated expression of expansion-related genes (PTGS2, TNFAIP6, and HAS2) in the COCs at 4 and 8 h of culture, with a significant decrease at 20 h of culture. Both AREG and EREG also increased expression of the expansion-related genes; however, the relative abundance of mRNA for each gene was much lower than in the FSH-stimulated COCs. In contrast to FSH, AREG and EREG neither stimulated expression of CYP11A1 in the COCs nor an increase in progesterone production by cumulus cells. AREG and EREG stimulated maturation of oocytes and expansion of cumulus cells, although the percentage of oocytes that had reached metaphase II was significantly lower when compared to FSH-induced maturation. Nevertheless, significantly more oocytes stimulated with AREG and/or EREG developed to blastocyst stage after parthenogenetic activation when compared to oocytes stimulated with FSH alone or combinations of FSH/LH or pregnant mares serum gonadotrophin/human chorionic gonadotrophin. We conclude that EGF-like peptides do not mimic all effects of FSH on the cultured COCs; nevertheless, they yield oocytes with superior developmental competence.
Keywords: epidermální růstový faktor; Gonadotropins; oogeneze; oocyty; partenogeneze; Cells, Cultured; Cell Proliferation; Cell Differentiation; zvířata; embryonální vývoj; Oogenesis; Peptide Fragments; Follicle Stimulating Hormone; Oocytes; kultivace embrya; proliferace buněk; Epidermal Growth Factor; Embryo Culture Techniques; Embryonic Development; Parthenogenesis; Swine; peptidové fragmenty; kumulární buňky; kultivované buňky; prasata; Cumulus Cells; ženské pohlaví; stanovení celkové genové exprese; Animals; gonadotropiny; Gene Expression Profiling; folikuly stimulující hormon; buněčná diferenciace; Female